The Marquis de Sade and the avant-garde - Mahon, Alyce (Princeton : Princeton University Press, 2020)
"This is the first book to examine the cultural history of Marquis de Sade's (1740-1814) philosophical ideas and their lasting influence on political and artistic debates. An icon of free expression, Sade lived through France's Reign of Terror, and his writings offer both a pitiless mirror on humanity and a series of subversive metaphors that allow for the exploration of political, sexual, and psychological terror. Generations of avant-garde writers and artists have responded to Sade's philosophy as a means of liberation and as a radical engagement with social politics and sexual desire, writing fiction modelled on Sade's novels, illustrating luxury editions of his works, and translating his ideas into film, photography, and painting. In The Sadean Imagination, Alyce Mahon examines how Sade used images and texts as forms that could explore and dramatize the concept of terror on political, physical, and psychic levels, and how avant-garde artists have continued to engage in a complex dialogue with his works. Studying Sade's influence on art from the French Revolution through the twentieth century, Mahon examines works ranging from Anne Desclos's The Story of O, to images, texts, and films by Man Ray, Pier Paolo Pasolini, Guillaume Apollinaire, Jean-Jacques Lebel, and Peter Brook. She also discusses writings and responses to Sade by feminist theorists including Angela Carter and Judith Butler. Throughout, she shows how Sade's work challenged traditional artistic expectations and pushed the boundaries of the body and the body politic, inspiring future artists, writers, and filmmakers to imagine and portray the unthinkable"--
Imported from: zcat.oclc.org:210/OLUCWorldCat (Do not remove)
boek
Keywords: Sade, -- marquis de, -- 1740-1814.; Sade, Donatien Alphonse François de, -- 1740-1814 -- Influence; Sade, Donatien Alphonse François de, -- 1740-1814; Experimentell konst; Influenser; Arts -- Experimental methods; Influence (Literary, artistic, etc.); Arts -- Experimental methods; Influence (Literary, artistic, etc.); Influence (Psychology)